Tsunamis - Stiefel, Chana, 1968- (New York : Children's Press, 2009)
An illustrated exploration of tsunamis that discusses why they occur, the damage caused by them, how the are studied, and other related topics; and includes statistics, resources, a glossary, and an index.
Out of the blue -- Tsunamis in motion -- Suviving the waves -- Nature's warning -- Cleaning up -- Preventing future disasters -- True statistics -- Resources -- Important words.
Includes bibliographical references (p. 44-45) and index.
5.3
3-6
3-6
Keywords: Tsunamis -- Juvenile literature; Tsunamis; Tsunamis